Similar Metabolic Health in Overweight/Obese Individuals With Contrasting Metabolic Flexibility to an Oral Glucose Tolerance Test - Fernández-Verdejo, Rodrigo; Malo-Vintimilla, Lorena; Gutiérrez-Pino, Juan; López-Fuenzalida, Antonio; Olmos, Pablo; Irarrazaval, Pablo; Galgani, Jose E. (Frontiers in Nutrition, 2021)
Background: Low metabolic flexibility (MetF) may be an underlying factor for metabolic health impairment. Individuals with low MetF are thus expected to have worse metabolic health than subjects with high MetF. Therefore, we aimed to compare metabolic health in individuals with contrasting MetF to an oral glucose tolerance test (OGTT). Methods: In individuals with excess body weight, we measured MetF as the change in respiratory quotient (RQ) from fasting to one hour after ingestion of a 75-g glucose load (i.e. OGTT). Individuals were then grouped into low and high MetF (Low-MetF n=12; High-MetF n=13). The groups had similar body mass index, body fat, sex, age, and maximum oxygen uptake. Metabolic health markers (clinical markers, insulin sensitivity/resistance, abdominal fat, intrahepatic fat) were compared between groups. Results: Fasting glucose, triglycerides (TG), and HDL were similar between groups. So were insulin sensitivity/resistance, visceral and intrahepatic fat. Nevertheless, High-MetF individuals had higher diastolic blood pressure, a larger drop in TG concentration during the OGTT, and a borderline significant (P=0.05) higher subcutaneous adipose tissue (SAT). Further, compared to Low-MetF, High-MetF individuals had an about 2-fold steeper slope for the relationship between SAT and fat mass index. Conclusion: Individuals with contrasting MetF to an OGTT had similar metabolic health. Yet high MetF appears related to enhanced circulating TG clearance and enlarged subcutaneous fat.